MicroRNA-126 mimic administration accelerates vascular perfusion recovery and angiogenesis in a hind limb ischemia model. (14th October 2021) - Theofilis, P; Vogiatzi, G; Oikonomou, E; Gazouli, M; Siasos, G; Katifelis, H; Perrea, D; Vavouranakis, M; Iliopoulos, D C; Tsioufis, C; Tousoulis, D
Abstract: Background: Peripheral arterial disease caused mainly by atherosclerosis portent significant morbidity, adverse prognosis and mortality, with localized treatment approaches aiming at symptom alleviation and improvement of circulation. Recently, scientific interest has been shifted towards epigenomics, with microRNAs appearing as a future therapeutic target in ischemic cardiovascular diseases due to their potential in regulating angiogenesis. Purpose: We investigated the pro-angiogenic effect of miRNA-126 mimic in an in vivo model of hind limb ischemia. Methods: Ten-week-old male C57Bl/6 mice (n=20) were subjected to left femoral artery ligation and were treated with microRNA-126 mimic at a dose of 5mg/kg (Group A, n=10) or 0.2ml normal saline (Group B, n=10) on days 1, 3 and 7. Laser Doppler imaging was performed to verify successful ligation on day 0 and to evaluate differences in the ischemic-to-normal (I/N) hind limb perfusion ratio on day 7 and 28. Muscle tissue expression of microRNA-126 and vascular endothelial growth factor (VEGF) was determined via PCR. Results: Following microRNA-126 mimic administration in Group A subjects, we noted a qualitative and quantitative stepwise increase in I/N hind limb perfusion ratio [Day 0: 0.354 (0.276, 0.455) vs. Day 8: 0.775 (0.700, 0.844) vs. Day 28: 0.681 (0.660, 0.896), p=0.001] (Figure 1, Panels A and B). In Group B a stepwise increase of lesser magnitude was observed in I/N hind limb perfusion ratio [Day 0: 0.267 (0.164, 0.383) vs. Day 8: 0.400 (0.338, 0.418) vs. Day 28: 0.539 (0.483, 0.603), p=0.074]. Importantly, over time changes of I/N hind limb perfusion ratio were significantly higher in group A compared to group B (p for interaction=0.005) (Figure 1, Panel B). Muscle tissue expression of microRNA-126 in the ischemic hind limb of Group A was 350-fold lower compared to the ischemic hind limb of Group B (p<0.001) (Figure 1, Panel C). A higher expression (14.2-fold) of VEGF in the ischemic hind limb of microRNA-126-treated mice compared to that of control group was detected (p<0.001) (Figure 1, Panel C). A statistically significant negative correlation was noted between microRNA-126 and VEGF tissue expression levels in the ischemic limbs of both Group A and B subjects whereas no correlation between microRNA-126 and VEGF was observed in the non-ischemic hind limbs of the entire study population (Figure 1, Panel D). Conclusion: MicroRNA-126 mimic delivery in the ischemic hind limb of mice can accelerate vascular perfusion recovery via angiogenesis, which is mediated by VEGF expression. FUNDunding Acknowledgement: Type of funding sources: None.